Development of innovations as a process of resource transformation into innovative results in tourism - D.M., D.M.; Levchenko, T.P.; Moldazhanov, M.B.; Amanbayeva , A.A. (BUKETOV BUSINESS REVIEW, 2019)
Most hotel organizations operate in the context of constant changes in consumer preferences, increasing competition and changing of technological requirements. To achieve business goals, such as increasing of profits and economic growth, it is necessary to carry out a continuous stream of successful innovations. Many foreign scientists, such as Buys, Agel, Gosselink, Van der Valk, argue that innovation is a prerequisite for the survival of hotel organizations. Their strategic position depends on the ability to offer quality services that meet market needs. Therefore, ensuring a continuous flow of effective innovation is essential. Many entrepreneurs are interested in finding ways to increase the intensity of innovation activities of their enterprises. The first problem to be encountered is that the intensity of innovation activity is a latent variable and therefore cannot be directly measured. It is necessary to solve the problem of measuring the intensity of innovation activity before we can explore ways to increase it. Many different techniques are used in economics, which provide considerable confusion and uncertainty in the study of the concept under consideration and also complicate its assessment. Thus, the purpose of this work is to develop and test a scale measuring of the intensity of innovation activity of hotel organizations.